Water analysis at Dearborn laboratory facility - Dearborn Chemical Company (1934)
General view of employee Al Slisg conducting a water analysis test at the Dearborn Chemical Company's 35th Street laboratory and manufacturing facility located in Chicago, Illinois. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Employees; Chemical industry; Scientific apparatus and instruments; Water purification chemicals industry; Corporations; Glassware; Laboratories; Dearborn Chemical Company; Water--Analysis; Water--Testing